The Application Of The Principle Of Good Faith In Online Transactions As An Effort To Protect The Law Against Consumers - Pawestri, Ros; Heniyatun, Heniyatun; Sulistyaningsih, Puji; Praja, Chrisna Bagus Edhita (Prosiding University Research Colloquium, 2021)
The principle of good faith is one of the efforts to provide legal protection to consumers inonlinetransactions. This research aims to review andauthorize theapplication of theprinciple of goodfaith, and its legal protectionif consumers are harmed in onlinetransactions. This research is expected to provide additional thought for all partiesinvolved in transactions through online. The method used in this study is normativejuridical, with data collection through literature studies and interviews. The resultsshowed that the application of the principle of good faith by business actors in transactionsthrough online is a very important thing, and must be implemented by the partiesconcerned, so that no party is lost. This is because good faith is the basis of business actorsin making agreements to minimize losses for consumers. But in practice there are stillmany consumers who are harmed by business actors. Legal protection of consumers isbased on Law No. 8 of 1999 on Consumer Protection and Law No. 19 of 2016 on changesto Law No. 11 of 2008 on Information and Electronic Transactions (ITE Law), namely whatare the rights and obligations of business actors and comments, and how the provisions ononline transactions to protect the interests of the parties. Legal efforts that can be done byconsumers are settlements on a non-litigation basis or litigation.